Measurement of jet activity produced in top-quark events with an electron, a muon and two b-tagged jets in the final state in pp collisions at [Formula: see text] TeV with the ATLAS detector - Aaboud, M; Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; et al. (The European physical journal. C, Particles and fields, 2017)
Measurements of jet activity in top-quark pair events produced in proton-proton collisions are presented, using 3.2 fb[Formula: see text] of pp collision data at a centre-of-mass energy of 13 TeV collected by the ATLAS experiment at the Large Hadron Collider. Events are chosen by requiring an opposite-charge [Formula: see text] pair and two b-tagged jets in the final state. The normalised differential cross-sections of top-quark pair production are presented as functions of additional-jet multiplicity and transverse momentum, [Formula: see text]. The fraction of signal events that do not contain additional jet activity in a given rapidity region, the gap fraction, is measured as a function of the [Formula: see text] threshold for additional jets, and is also presented for different invariant mass regions of the [Formula: see text] system. All measurements are corrected for detector effects and presented as particle-level distributions compared to predictions with different theoretical approaches for QCD radiation. While the kinematics of the jets from top-quark decays are described well, the generators show differing levels of agreement with the measurements of observables that depend on the production of additional jets.